Probabilistic Analysis of Structures Under Snow Load - Severyn, Vitaliy; Pashchenko, Andrii; Mytrofanov, Pavel (International Journal of Engineering and Technology, 2018)
The authors of the article present a model of snow load on the construction of buildings and structures for the territory of Ukraine. This model can be used for others countries of the world. Numeric probabilistic models of snow load have been worked out for PC. The digital snow load model was developed based on observations of many Ukrainian weather stations. This model is implemented as a software package in the programming language C ++. The results of snow load simulation can be used to assess the reliability of building structures. Finally, the implementation of this algorithm will allow to calculate the reliability of a number of existing designs. The received reliability forecasts will allow to reveal potentially dangerous types of building structures and to justify on their basis a proposal to improve Code calculations. Â